PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI MELALUI KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI PT. ANJUR NAULI MEDAN - Lyandru Togumulia Tambunan (Akademi Pariwisata Darma Agung, 2020)
The objective of the research was to analyze leadership style and organizational culture on employees, satisfaction, either directly or indirectly, through employees job satisfaction as intervening variable. The research was conducted at PT. Anjur Nauli, Medan, a local company which operates in contractor service and housing development. It used descriptive quantitative and explanatory research method, supported by a survey. The population and the samples were 30 employees of PT. Anjur Nauli as the respondents. The data were gathered by conducting documentary study and distributing questionnaires and analyzed by using path analysis which consisted of direct and indirect influence. F-test was used to test the hypothesis simultaneously, and t-test for testing the hypothesis partially. The result of the hypothesis test showed that, directly, the variable of leadership style and organizational culture had positive and significant influence on employees performance. Job satisfaction as an intervening variable had positive and significant influence on employees performance. The variable of leadership style and organizational culture had positive and significant influence on employees performance through job satisfaction as intervening variable. It was also found that direct influence of leadership style and organizational culture was more significant on employees performance than through job satisfaction as intervening variable. It is recommended that the company pay attention to the factors which can increase leadership style, organizational culture, and job satisfaction because these variables will be able to increase the employees performance PT. Anjur Nauli, Medan.